ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2012 – 2014) - Nemia Kulamega Abugau, 11.05.52.0209; Maryono, Maryono (Students' Journal of Accounting and Banking, 2016)
This study aims to identify and analyze the effect of firm size, institutional ownership, dividend policy and the free cash flow to debt policy. The research sample with the criteria that have been determined acquired a total of 17 manufacturing companies that go public in Indonesia Stock Exchange for 3 years, so the data is processed as many as 51 data. Methods of research data analysis using linear regression. The test results showed that there was a positive effect but significant correlation between the size of the company against debt policy, there is a negative effect but not significant between institutional ownership of the debt policy, there is a negative effect but not significant between dividend policy on debt policy, and there is a positive effect but not significant between free cash flow for debt policy. Keywords: Company Size, Institutional Ownership, Dividend Policy, Free Cash Flow, Debt Policy